Investigations of spin Hamiltonian parameters and local structures for three Cr(CN)63− centres in NaCl at three temperatures. (14th December 2015) - Dong, Hui-Ning; Liu, Xu-Sheng; Zhou, Hong-Fei
Graphical abstract: We have studied SHPs and local structures for all centers at various temperatures uniformly from perturbation calculations for a rhombic or orthorhombic 3 d 3 cluster. The local structures were analyzed in view of cation vacancies. Temperature dependences of ZFSs, Δ R ‾ and H are clarified. CT contributions to g factors are involved. Abstract: The spin Hamiltonian parameters (g factors and zero-field splittings (ZFSs)) and local structures of three Cr(CN)6 3− centres in NaCl are studied at three temperatures based on the perturbation calculations. The signs and magnitudes of the ZFSs D and E are in accordance with those of average bond length discrepancy Δ R ‾ ( = ( 1 / 6 ) ∑ δ R i, i = 1 – 6 ) and rhombic distortion parameter H ( = - ( Δ φ ‾ ) 1 / 2 ( Δ R ‾ ) 3 / D ), relevant to average planar bond angle discrepancy Δ φ ‾ ( = ( 1 / 4 ) ∑ δ φ i, i = 1 - 4 ) related to an ideal octahedron. The SHPs exhibit the smallest rhombic (or orthorhombic) distortions and the weakest covalency at 4.2 K, and the largest rhombic distortions and strongest covalency at 77 K with comparable D and E. The magnitude of g-shifts (= gi − gs ) obey the tendency 77 K < 290 K ⩽ 4.2 K, in consistent with that of covalency factor N . The CT contributions to g-shifts are opposite in sign and about 51–63% in magnitude compared with the CF ones. The microscopic mechanisms of the local structures (i.e., the impurity displacements Δ R X and Δ R Y and ligand displacements Δ R P, Δ R P ′ and Δ R P ″) are analyzed for the various centres in view of the electrostatic interactions arising from the cation vacancies. Unlike conventional rhombic centres I and II for all three temperatures, the new orthorhombic centre III occurs only at low temperatures (4.2 K and 77 K) and indeed exhibits new structural properties, especially the largest Δ R ‾ and H as well as D and E.